2021
DOI: 10.1016/j.eswa.2021.115805
|View full text |Cite
|
Sign up to set email alerts
|

CovH2SD: A COVID-19 detection approach based on Harris Hawks Optimization and stacked deep learning

Abstract: Starting from Wuhan in China at the end of 2019, coronavirus disease (COVID-19) has propagated fast all over the world, affecting the lives of billions of people and increasing the mortality rate worldwide in few months. The golden treatment against the invasive spread of COVID-19 is done by identifying and isolating the infected patients, and as a result, fast diagnosis of COVID-19 is a critical issue. The common laboratory test for confirming the infection of COVID-19 is Reverse Transcription Polymerase Chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 91 publications
(77 reference statements)
0
23
0
3
Order By: Relevance
“…In some problems, dropout layer is used and it is very helpful to overcome the overfitting problems of networks. Parameter optimizer plays a main role in calculating the performance of CNN [ 46 ]. The working of layers of CNN is expressed in Figure 2 .…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In some problems, dropout layer is used and it is very helpful to overcome the overfitting problems of networks. Parameter optimizer plays a main role in calculating the performance of CNN [ 46 ]. The working of layers of CNN is expressed in Figure 2 .…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Balaha et al [214] tried to propose an approach, called CovH2SD, in order to detect COVID-19 from chest Computed Tomography (CT) images. They applied transfer learning techniques using nine convolutional NNs, namely: ResNet101, ResNet50, VGG16, VGG19, MobileNetV1, MobileNetV2,Xception, DenseNet121, and DenseNet169.…”
Section: Coronavirus Covid-19mentioning
confidence: 99%
“…Alternatively, various types of radiological imaging exist such as X-rays and the computed tomography (CT) to identify patients affected by pneumonia due to COVID-19 infection. It is reported that COVID-19 patients' lungs exhibit some visual features, such as markings and spots, that may distinguish COVID-19 positive cases from normal cases using radiological images ( Balaha et al, 2021 ). Unlike RT-PCR and CT, chest X-ray is cheaper, less time consuming, and it is readily available for COVID-19 screening.…”
Section: Introductionmentioning
confidence: 99%